Flux of amino acids and energy substrates across the leg in weight-stable HIV-infected patients with acute opportunistic infections: indication of a slow protein wasting process - Breitkreutz, Raoul; Wagner, Jens; Tokus, Mehmet; Benner, Axel; Rossol, Siegbert; Pittack, Nicole; Stein, Jürgen; Dröge, Wulf; Holm, Eggert (Journal of molecular medicine, 2001)
Increased whole-body proteolysis with muscle protein net degradation has been suggested as one of the causes of weight loss in patients infected with human immunodeficiency virus (HIV). We studied the exchange rates of amino acids and energy substrates across the lower extremity in 16 HIV patients and 16 age-matched controls with similar body cell mass. The patients had either opportunistic infections or chronic diarrhea but no signs of clinical malnutrition. The following findings were obtained in the HIV patients: an augmented peripheral net release of arginine and lysine; an increase in both the negative arterial-venous difference and the efflux of the nitrogen contained in nonmetabolized amino acids; diminished export of 3-methylhistidine; lowered plasma and erythrocyte amino acid concentrations; reduced output of glycerol and furthermore; and neither a net release nor a net uptake of free fatty acids. The findings concerning nitrogen metabolism support the hypothesis that, in the presence of a reduction in protein breakdown, peripheral protein synthesis is severely depressed, making a slow protein wasting process likely to occur. The balances of glycerol and free fatty acids are due not only to the leg tissues but perhaps also in part to increased net retention of these substrates by skeletal muscle.